Seakeeping Test of Ship Perambuan Model at Maneuovering and Ocean Engineering Basin (MOB) Laboratory for Hydrodynamics Technology - Rizal, Nandiko (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Pure experiments done at Laboratory for Hydrodynamics Technology, in the form of seakeeping test of ship perambuan model at full load condition to obtain motion data of ship model recorded by using wireless optical tracking system. With wireless optical tracking system is expected to be more able to describe the phenomenon of motions the ship while sailing. Seakeeping test ship perambuan model is done at Maneuovering and Ocean Engineering Basin (MOB), in irregular wave conditions with significant wave heights Hs = 2.0 m and peak wave period Tp = 8.0 sec at the direction of wave relative to the direction of the ship 180 deg and 135 deg. Measurement of motion of the ship includes 6 DoF (Degree of Freedom) motions that is surge, sway, heave, roll pitch and yaw. Statistical analysis of measurement results is presented in order to know the quality of the ship motion. To support the analysis, the measurement results are also displayed in the Response Amplitude Operator, RAO.